Thermally conductive epoxy/boron nitride composites with high glass transition temperatures for thermal interface materials. (15th December 2021) - Yue, Cheng'e; Guan, Lizhu; Zhang, Xiaorui; Wang, Yubo; Weng, Ling
Graphical abstract: Highlights: Polymer composites were prepared using heat-resistant epoxy and functionalized BN.. The Tg increased from 257 to 275 °C upon addition of 30 wt% functionalized BN. With 30 wt% functionalized BN, the linear expansion coefficient decreased by 15%. The composite with 30 wt% BN exhibited enhancement of 142% in thermal conductivity. The composite with 30 wt% BN exhibited shear strength of 11.6 MPa up to 150 °C. Abstract: Thermally conductive polymer composites with high glass transition temperatures ( T g ) are of interest for electronic devices in aerospace applications. Here, epoxy/boron nitride (BN) composites were fabricated using a highly heat-resistant epoxy as a polymer matrix and epoxysilane functionalized BN as thermally conductive filler. These composites exhibited excellent processability and high T g of up to 275 °C. Moreover, the linear expansion coefficient ( α ) of the composite with a BN content of 30 wt% (48.89 × 10 −6  °C −1 ) was 15% smaller than that of the pristine epoxy. The use of epoxysilane functionalized BN provided improved dispersibility in the epoxy matrix, thus reducing the interface thermal resistance and increasing the thermal conductivity. The thermal conductivity of the composite containing 30 wt% BN was 142% higher than that of the epoxy alone at 25 °C, and this excellent thermal conductivity was maintained at temperatures up to 150 °C. Furthermore, the single-lap shear strength at 150 °C reached 11.66 MPa. Notably, the prepared thermally conductive composite with outstanding thermal management characteristics exhibited excellent performance when used as a thermal interface material for electronic devices.